Islamic Law Review on the Role of Gampong in Resolving Adultery Cases in North Aceh - Mizaj Iskandar Usman (al-Afkar, Journal For Islamic Studies, 2026)
This study examines the role of Gampong customary institutions in resolving adultery cases in North Aceh and analyzes their conformity with Islamic criminal law as regulated in Aceh Qanun No. 6 of 2014 concerning Islamic Criminal Code. The research employs a qualitative method using normative and empirical legal approaches. Data were collected through in-depth interviews, observation, and focus group discussions conducted in three Gampongs: Meunasah Blang, Paya Leupah, and Keude Krueng. The findings reveal that Gampong institutions function not only as local administrative structures but also as socio-religious mechanisms for maintaining public morality, social harmony, and communal order. The settlement of adultery cases at the village level emphasizes deliberation, mediation, moral guidance, and restorative justice rather than punitive measures. The study further demonstrates that customary settlements are generally applied in cases categorized as khalwat or moral misconduct that do not fulfill the evidentiary requirements of zina under Islamic law. However, cases considered to meet the legal elements of jarimah are referred to the Wilayatul Hisbah and subsequently processed through the Sharia Court. This research concludes that the interaction between customary law and formal Sharia law in North Aceh reflects a dynamic model of legal pluralism that integrates Islamic values, local wisdom, and social restoration in resolving moral offenses.